Valor do controle corporativo no Brasil - Gonzalez Moyano, Rafael (2017)
This study is about premiums paid for corporate control in mergers and acquisitions in Brazil whose target company had, at the transaction date, shares traded on the stock exchange. This issue is relevant because it influences the amounts paid for equity interest when there is a change in corporate control, indicating that, under certain circumstances, the market value per share traded in the market may not represent its fair or trading value. This work analyzed the impacts in the premiums paid for corporate control caused by certain characteristics of the companies involved in those transactions, such as the size and degree of leverage of target companies, total shares acquired and the existence of foreign investors as the acquirer in part of those transactions. As a result, an average premium of 17.78% was paid for the acquisition of corporate control in publicly traded companies in Brazil. In addition, this study suggests that the size and degree of leverage of the target company positively influences the premium offered, while there is no statistical evidence that the total equity interest acquired and the existence of a foreign investor can influence the dimension of this premium